Growth performance and carcass characteristics of Tanzanian goats fed Chloris gayana hay with different levels of protein supplement - Mtenga, L.A.; Kitaly, A.J. (Elsevier, 1990)
Twenty-four growing indigenous Tanzanian male goats were studied in a completely randomized design experiment with four treatment groups for growth rate, feed conversion ratio (FCR), dressing percentage and carcass composition. The four groups of goats were fed hay ad libitum (A) and hay ad libitum with 200 g/day of concentrate supplement containing 102, 150 or 177 g CP/kg DM (B, C, and D). Protein (CP) supplementation resulted in increased total dry matter intake and decreased feed conversion ratio. Compared with the control group (A), animals on treatment D had the highest growth rate (62.51 +_8.01 vs. 22.61+_ 10.91 g/day) and a superior feed conversion ratio (8.81+_1.30 vs. 22.81+_ 11.65 g DM intake / g gain). Daily crude protein and digestible energy intake increased with higher protein levels. Supplemented goats had significantly higher dressing percentage and fat depot percentages in kidney and gut. Lean meat percentages were 62.6±2.50, 64.2±0.89, 60.9±3.44 and 63.3±1.90 for treatments A, B, C and D, respectively. Control goats had significantly lower proportions of fat and higher proportions of bone. There was little indication that protein level in supplements affected the composition of carcasses.